ASSISTANCE OF BANANA CHIPS MSMES DURING THE COVID-19 PANDEMIC USING ONLINE MARKETING AND BUSINESS LICENSES - Encep Saefullah; Anggita Arkin Dwi Pradita; Mula Martogi J Purba; Bobi Martono; Syifa Fauziah; Rahmawati Aulia (Yayasan Education and Social Center, 2021)
The COVID-19 pandemic is still ongoing, the outbreak of this virus does not only hit the health sector and public services, even worse, it has the potential to paralyze various sectors of human life, including the micro, small and medium enterprise (MSME) sector. This phenomenon is also very impactful and felt by MSME actors in Kamurang Village, Cikande District, Serang Regency whose type of business is very dependent on the turnover of money from the sale of merchandise. Partners in this service program are Banana Chips SMEs..This community partnership program aims to provide knowledge in terms of MSME management, innovations related to optimizing online product marketing media in order to maximize marketing or sales, and the process of applying for business licenses in order to obtain a Business Identification Number (ID Number). Micro Small Business Permit (NIB) (IUMK). This is based on issues with administration and usage of online media in terms of marketing identified by MSMEs themselves, as well as the lack of a government-issued company license. As a result of this activity, MSME actors' knowledge and understanding of MSME management increased, as did their use of social media (Instagram and Facebook) and chat apps (Whatsaap) as online marketing tools, as well as their ability to obtain a Business Identification Number (NIB) or Micro Small Business License. (IUMK) and product developments, such as flavor and packaging variations, are becoming more diverse. By using a positive approach in the form of a participatory, reflective and innovative approach, banana chips SMEs are expected to be able to compete with other types of businesses.